Manifestations and Outcome of Cardiac Sarcoidosis and Idiopathic Giant Cell Myocarditis by 25-Year Nationwide Cohorts - Nordenswan Hanna‐Kaisa; Lehtonen Jukka; Ekström Kaj; Räisänen‐Sokolowski Anne; Mäyränpää Mikko I.; Vihinen Tapani; Miettinen Heikki; Kaikkonen Kari; Haataja Petri; Kerola Tuomas; Rissanen Tuomas T.; Kokkonen Jorma; et al. (WILEY, 2022)
Background
Cardiac sarcoidosis (CS) and giant cell myocarditis (GCM) share many histopathologic and clinical features. Whether they are parts of a one-disease continuum has been discussed.
Methods and Results
We compared medical record data of 351 CS and 28 GCM cases diagnosed in Finland since the late 1980s and followed until February 2018 for a composite end point of cardiac death, aborted sudden death, and heart transplantation. Heart failure was the presenting manifestation in 50% versus 15% (P<0.001), and high-grade atrioventricular block in 21% versus 43% (P=0.044), of GCM and CS, respectively. At presentation, left ventricular ejection fraction was <= 50% in 81% of cases of GCM versus in 48% of CS (P=0.004). The median (interquartile range) of plasma NT-proBNP (N-terminal pro-B-type natriuretic peptide) was 5273 (2782-11309) ng/L on admission in GCM versus 859 (290-1950) ng/L in CS (P<0.001), and cardiac troponin T exceeded 50 ng/L in 17 of 19 cases of GCM versus in 48 of 239 cases of CS (P<0.001). The 5-year estimate of event-free survival was 77% (95% CI, 72%-82%) in CS versus 27% (95% CI, 10%-45%) in GCM (P<0.001). By Cox regression analysis, GCM predicted cardiac events with a hazard ratio of 5.16 (95% CI, 2.82-9.45), which, however, decreased to 1.58 (95% CI, 0.71-3.52) after inclusion of markers of myocardial injury and dysfunction in the model.
Conclusions
GCM differs from CS in presenting with more extensive myocardial injury and having worse long-term outcome. Yet the key determinant of prognosis appears to be the extent of myocardial injury rather than the histopathologic diagnosis.